Development of an integrated system design tool for helical Vertical Axis Wind Turbines (VAWT-X). (November 2022) - Lu, Brandon; Zanj, Amir
Abstract: Vertical Axis Wind Turbine (VAWT) technology has been identified to be a potential disruptor to the wind energy industry. However, this technology is yet to deliver the promised performance, mainly due to its system design. To help designers reveal the VAWTs' technological potential, the current study focuses on developing a physics-based, interrelated multi-domain dynamic model of the whole system to be used for systematic design optimisation and integrated system performance analysis. To achieve this the subsystems and design parameters of a typical VAWT are first identified. Then by dynamically coupling domain-independent models of the involved components with DMST, an integrated parametric modelling platform is generated and executed in MATLAB/Simulink. The developed parametric tool is then validated at a system level using performance data from a 6kW VAWT-X Energy case study turbine, showing a high level of accuracy and robustness. Finally, the system dynamics are studied through sensitivity analyses to evaluate the suitability of the platform for further dynamic analysis and design optimisation. The simulated results indicate the existence of component interaction induced dynamics with significant impact on system performance if neglected. Highlights: Domain independent modelling provides dynamics interfaces between multidisciplinary subsystems revealing the subsystem dynamic interactions. Subsystem interactions can alter system performance while the system experiencing a dynamic transition. Performance of a multi component system can be improved by modifying the design specifications of its components regarding to their system performance.